(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Sedimentary clay of three Latvia region of Latgale lakes – Zeiļi, Pauguļi and Plusons – was investigated. Mineral composition was determined by X-ray diffraction, the average size and size distribution of particles by dynamic light scattering method, specific surface by Brunauer-Emmett-Teller method, and adsorption characteristics after methylene blue: adsorption capacity and adsorption isotherms. The samples contained typical clay crystalline phases – illite, kaolinite – and rock forming minerals – quartz, dolomite, calcite, plagioclase, albite, and enstatite. The granulometric content of samples is mostly characterised by silt (2 – 63 µm) and clay (< 2 µm) fractions. Specific surface area varied from 9.45 to 20.68 m2/g. The adsorption capacity of lake clay was in the range of 25.8 – 45.8 mg/g. Clay adsorption isotherms were represented by the second and fifth type curves according to the International Union of Pure and Applied Chemistry (IUPAC) classification, indicating the presence of micro- and macroporous space in samples and strong intermolecular interactions. The difference between properties of clay in different lakes and at different depths and their influencing factors have been clarified. The information obtained enables to predict the areas of use of clay in cosmetics and medical treatment.